Manajemen Pendidikan Ramah Anak dalam Lembaga Pendidikan Islam - Abidin, Zainal; Imaduddin, Imaduddin; Hamzah, Akhmad Fauzi (LP. Ma'arif Janggan Magetan, 2022)
Child-friendly education is an educational model that aims to fulfill the rights of the child by providing a comfortable, safe and enjoyable learning environment for both students and teachers. In addition, it enables the participants to learn independently. Because all rules created by educational institutions must include student participation. This context relates to both the students' freedom to express their ideas and the participants' freedom to reach their full potential. This study uses a library-based research methodology using books and scholarly articles on child-friendly schools. The aim of this study is to describe child-friendly education in Islamic educational institutions. In order to realize child-friendly education in educational institutions, we must first develop some components, including the child-friendly school policy. Educators and educational staff are aware of children's rights, child-friendly teaching and learning processes, non-violent discipline and child-safe facilities and infrastructure.